Insect community structure in the Baixo Vouga Lagunar saltmarshes : influence of saline intrusion and sea level rise - Bastos, Miguel Angelo (2020)
Climate change is affecting many ecosystems worldwide and one of the most striking evidences is sea level rise. Saltmarsh areas provide important ecosystem services, however, saline intrusion, one of the consequences of sea level rise, can lead to important changes in the composition of plant and animal communities, with consequences for the ecosystem services provided. Baixo Vouga Lagunar (BVL) at Ria de Aveiro has been impacted by saline intrusion in certain areas due to changes in hydrodynamics and tidal prism, which may be exacerbated in the future due to sea level rise. Changes in plant composition have already been observed, namely replacement of species by others more tolerant to salinity and longer flooding periods. Invasion and proliferation of invasive plants such as Spartina versicolor was also observed at BVL. This work aimed to characterize the insect communities that inhabit this biotope, to understand how saline intrusion influences the floristic composition in the BVL and to understand how the insect communities react to the differences associated with the diversity of halophytes present, in response to the salinity gradients. Four transects were established at BVL and plant species composition was recorded. Along these transects, soil was also characterized, pitfall traps were installed to capture epigeal insects and sweep-nets were used to collect aerial insects. All the insects collected were morphologically characterized and identified. Nine different insect orders were recorded, where the most diverse were Coleoptera, Diptera and Hemiptera. It was verified that the floristic diversity and the presence of invader species as Spartina versicolor influenced the insect communities.